Core nitrogen cycle of biofoulant in full-scale anoxic & oxic biofilm-membrane bioreactors treating textile wastewater. (April 2021) - Zhou, Lijie; Zhao, Bikai; Ou, Pingxiang; Zhang, Wenyu; Li, Haixiang; Yi, Shan; Zhuang, Wei-Qin
Graphical abstract: Highlights: Core nitrogen cycle of biofoulant in MBR treating textile wastewater was studied. Biofoulant was without nitrification and anammox due to missing AmoCAB and Hao. 15 species contained whole DNRA pathway with nitrate reductase & nitrite reductase. DNRA (majority) & denitrification (minority) were core nitrogen cycle of biofoulant. DNRA caused NH4 + -N increase after membrane filtration to treat textile wastewater. Abstract: Core nitrogen cycle within biofoulant in full-scale anoxic & oxic biofilm-membrane bioreactor ( b MBR) treating textile wastewater was investigated. Wastewater filtered through membrane with biofoulant had elevated NH4 + -N and NO2 − -N concentrations corresponding to decreased NO3 − -N concentrations. Nevertheless, total nitrogen concentrations did not change significantly, indicating negligible nitrogen removal activities within biofoulant. Metagenomic analysis revealed a lack of genes, such as AmoCAB and Hao in biofoulant, indicating absence of nitrification or anammox populations. However, genes encoding complete pathway for dissimilatory nitrate reduction to ammonium (DNRA) were discovered in 15 species that also carry genes encoding both nitrate reductase and nitrite reductase. No specie contained all genes for complete denitrification pathway. High temperature, high C:N ratio, and anoxic conditions of textile wastewater could favorite microbes growth with DNRA pathway over those with canonical denitrification pathway. High dissolved oxygen concentrations could effectively inhibit DNRA to minimize ammonia concentration in the effluent.